Brand loyalty through engagement: Effects of content marketing and brand experience - Rahma, Faiza; Dewi, Reni Shinta (Journal of Management and Business Education, 2025)
Digitization is changing consumer behavior from offline to online. Social Media can generate curiosity and interest among the audience, so it can generate sales volume and brand loyalty. Similarly, what happened to the FMCG industry, one of which is Wardah. But based on market share and TBI (Top Brand Index), Wardah can’t be the first. This study aims to determine the effect of content marketing and brand experience on brand loyalty with customer engagement as an intervening variable. The type of this study is explanatory research with nonprobability sampling purposive sampling. Data analysis using SmartPLS4. The results of this study support the theory of consumer behavior. It can be applied in higher education curricula to enhance topics related to digital marketing strategies, consumer behavior, and brand management. The test results showed that content marketing, brand experience, and customer engagement significantly affect brand loyalty with a type of partial mediation. The recommendations of this study are fresh marketing in TikTok Wardah content, highlighting the uniqueness of the brand, efforts to keep consumers always involved, and innovating to maintain and improve quality so that consumers remain loyal.